Multiplicative Topological Properties on Degree Based for Fourth Type of Hex-Derived Networks. (10th May 2022) - Ali, Haidar; Dustigeer, Ghulam; Li, Yong-Min; Shafiq, Muhammad Kashif; Ali, Parvez
Abstract : Chemical graph theory is a subfield of graph theory that uses a molecular graph to describe a chemical compound. When there is at least one connection between the vertices of a graph, it is said to be connected. Topology of graph has been expressed by numerical quantity which is known as topological index. Cheminformatics is a product field that combines chemistry, mathematics, and computer science. The graph plays a key role in modelling and coming up with any chemical arrangement. In this paper, we computed the multiplicative degree-based indices like Randić, Zagreb, Harmonic, augmented Zagreb, atom-bond connectivity, and geometric-arithmetic indices for newly developed fourth type of hex-derived networks and also present the graphical representations of results.